The mesospheric quasi-2-day wave over Tirunelveli(8.7degree N) - Gurubaran, S.; Sridharan, S.; Ramkumar, T.K.; Rajaram, R. (My University, 2001)
Observations of the quasi-2-day planetary wave over a period of two years with the medium frequency (MF) radar operated at Tirunelveli , India, are presented. The observational aspects of the characteristics of the wave over the low latitude station and its possible interaction with the mean wind and the diurnal tide are studied in detail. The amplitude of the 2-day wave has been observed to be larger in winter than in summer with noticeable inter-annual variability. The period of the wave varied between 46 and with a dependence on season. The vertical wavelength during large-amplitude wave bursts has been observed to be in the range of 35–. The clear anti-correlation between the diurnal tide and the quasi-2-day wave occurrences and the presence of the 16-h wave provide indications for their interaction, which might have extracted energy from the primary diurnal tide. The changes in the mean wind during the passage of the quasi-2-day wave reflect the importance of the wave in determining the mesospheric momentum budget.
Keywords: MF radar; Baroclinic instability; Wave number; Evanescent mode; Vertical wavelength; Wave–wave; Wave–meanflow interaction